Pengelolaan Lahan Kelapa Sawit Spesifik Lokasi di Desa Pengadang Kabupaten Sanggau - Arief, Fiera Budiarsyah; Fadilla, Ulfia; Sulakhudin, Sulakhudin; Widiarso, Bambang (Abdimas Mandalika, 2026)
Abstract:  Waterlogging in the Tunas Benih farmer group area has led to a significant decline in productivity, particularly in oil palm plantations older than 10 years. A site-specific land management approach has been implemented as a solution, involving improvements in drainage and irrigation systems through the construction of field drainage channels (worm trench drainage systems). The purpose of this program was to conduct outreach and provide assistance to smallholder oil palm farmers who experience waterlogging, particularly those in the Tunas Benih farmer group. The intervention employed an alternative participatory method using the Participatory Rural Appraisal (PRA/RRA) approach, which actively involved farmers from problem identification to solution implementation. The activities were conducted in three main stages: (1) initial outreach with the farmer group leader to establish communication and identify key issues, (2) technical dissemination discussing management alternatives for waterlogged land, including micro-drainage construction and adaptive fertilization strategies, and (3) monitoring and evaluation through interviews to assess changes in farmers’ knowledge and skills. The results of the program demonstrated a significant improvement in farmers’ understanding of the importance of drainage management and appropriate fertilization strategies to increase oil palm productivity. The program also created opportunities for income diversification through intercropping, thereby supporting household income and food security. Program sustainability requires continued technical assistance, improved access to production inputs, and the establishment of a farmer-led monitoring system.Abstrak: Genangan pada lahan kelompok tanai tunas benih menyebabkan penurunan produktivitas drastis terutama pada tanaman berusia lebih dari 10 tahun. Solusi yang diterapkan dengan pendekatan pengelolaan lahan spesifik lokasi melalui perbaikan sistem drainase dan irigasi dengan pembuatan saluran drainase paritan cacing. Tujuan kegiatan ini melakukan sosialisasikan  dan pendampingan kepada petani sawit dengan lahan tergenang pada kelompok tani Tunas Benih. Alternatif penanganan Metode pelaksanaan menggunakan pendekatan partisipatif dengan teknik Participatory Rural Appraisal (PRA/RRA) yang melibatkan petani secara aktif dalam identifikasi masalah hingga implementasi solusi. Kegiatan dilaksanakan melalui tiga tahap utama: sosialisasi awal dengan ketua kelompok tani untuk membangun komunikasi dan identifikasi permasalahan, sosialisasi teknis yang membahas alternatif penanganan lahan tergenang dengan materi pembuatan saluran drainase dan strategi pemupukan adaptif, serta monitoring dan evaluasi melalui wawancara untuk mengukur dampak program terhadap pengetahuan dan keterampilan petani. Hasil program menunjukkan peningkatan signifikan pemahaman petani tentang pentingnya pengelolaan drainase dan strategi pemupukan tepat untuk meningkatkan produktivitas kelapa sawit. Program juga membuka peluang diversifikasi usaha melalui tanaman sela untuk meningkatkan pendapatan dan ketahanan pangan petani. Keberlanjutan program memerlukan pendampingan intensif, fasilitasi akses sarana produksi, dan pembentukan sistem monitoring mandiri oleh kelompok tani.